Method to generate high efficient devices which emit high quality light for illumination - (:unkn) unknown (Osram Opto Semiconductors GmbH (Regensburg, DE), 2009)
An electroluminescent apparatus includes an OLED device emitting light in the blue and green spectrums, and at least one down conversion layer. The down conversion layer absorbs at least part of the green spectrum light and emits light in at least one of the orange spectra and red spectra.
Keywords: Engineering; Light Conversion (313/501); Light emitting diodes; Solid-state Type (313/498); Lighting systems; Organic Phosphor (313/504); Plural Layers (313/506); Design; Electroluminescence; With Envelope Or Encapsulation (313/512); Visible radiation; H01J 1/62 (20060101); H01J 63/04 (20060101); Color